Limited genotypic and geographic variability of 16-O-methylated diterpene content in Coffea arabica green beans. (1st November 2020) - Portaluri, Vincent; Thomas, Freddy; Guyader, Sophie; Jamin, Eric; Bertrand, Benoit; Remaud, Gérald S.; Schievano, Elisabetta; Mammi, Stefano; Guercia, Elena; Navarini, Luciano
Graphical abstract: Abstract: The acknowledged marker of Robusta coffee, 16-O-methylcafestol (16-OMC), can be quantified by NMR as a mixture with 16-O-methylkahweol (16-OMK), which accounts for approximately 10% of the mixture. In the present study, we detected and quantified 16-O-methylated diterpenes (16-OMD) in 248 samples of green Coffea arabica beans by NMR. We did not observe any differences between genotypes introgressed by chromosomal fragments of Robusta and non-introgressed genotypes. Environmental effects suggesting a possible protective role of 16-OMD for adaptation, as well as genotypic effects that support a high heritability of this trait were observed. Altogether, our data confirmed the presence of 16-OMD in green Arabica at a level approximately 1.5% that of a typical Robusta, endorsing the validity of 16-OMD as a marker for the presence of Robusta.